Desmoralizando el trabajo: Análisis del Objetivo Prioritario N°5 de la Política Nacional de Competitividad y Productividad (PNCP) desde la Antropología Económica - Tello Asencio, Jennifer (Pontificia Universidad Católica del Perú, 2022)
This article aims to present an analysis of the Priority Objective N°5 of the National Competitiveness and Productivity Policy (NCPP) from the perspective of economic anthropology. This objective refers to the creation of conditions to enable the Peruvian labor market to be more dynamic and competitive and to generate decent employment. To do this, we resort to key concepts used in this branch of anthropology, such as the labor theory of value (Marx, 1975; Collins, 2016), that of accumulation by dispossession (Kasmir and Carbonella, 2014), precariousness (Castel, 2014), as well as the theoretical approach of the moral economy (Carrier, 2018; Thompson, 1991; Scott, 1977; Palomera and Vetta, 2016). In the first part, the main aspects of the diagnosis of the Peruvian labor market from the NCPP are presented. Next, the policy measures proposed in the National Competitiveness and Productivity Plan are examined to determine how they fulfill the objective. Afterwards, the NCPP design and approval process is explored. Finally, it is concluded that the approval of this policy should be understood as part of a larger-scale process that aims to stripping workers of their non-wage labor benefits. This dispossession makes workers’ lives precarious and weakens the moral component of the Peruvian economy, that is, respect for the fulfillment of the obligations that people contract with each other in the framework of social relations and economic transactions.

El presente artículo tiene como objetivo exponer un análisis del Objetivo Prioritario N°5 de la Política Nacional de Competitividad y Productividad (PNCP) desde la perspectiva de la antropología económica. Dicho objetivo refiere a la creación de condiciones para que el mercado laboral peruano sea más dinámico y competitivo y pueda generar empleo digno para la población. Para ello, se recurre a conceptos claves empleados en esta rama de la antropología, como la teoría del valor-trabajo (Marx, 1975; Collins, 2016) el de acumulación por despojo (Kasmir y Carbonella, 2014), y precariedad (Castel, 2014), así como el enfoque teórico de la economía moral (Carrier, 2018; Thompson, 1991; Scott, 1977; Palomera y Vetta, 2016). En la primera parte se presentan los principales aspectos del diagnóstico del mercado laboral peruano consignado en la PNCP. Seguidamente, se examinan las medidas políticas propuestas para determinar cómo cumplen con el objetivo. Posteriormente, se exploran el proceso de diseño y aprobación de la PNCP. Finalmente, se concluye que la aprobación de esta política debe entenderse como parte de un proceso de mayor escala orientado a despojar a los trabajadores de sus prestaciones laborales no salariales. Dicho despojo precariza la vida de los trabajadores y debilita el componente moral de la economía peruana, es decir, el respeto por el cumplimiento de las obligaciones que las personas contraen entre sí en el marco de las relaciones sociales y las transacciones económicas.
Demoralizing labor: Analysis of Priority Objective No. 5 of the National Competitiveness and Productivity Policy (NCPP)
Keywords: Moral economy; Precariousness; Accumulation by dispossession; Labor; Economía moral; Precariedad; Acumulación por despojo; Trabajo; https://purl.org/pe-repo/ocde/ford#5.04.03